2011
DOI: 10.1007/s10646-011-0660-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of estrogenic contamination and biological effects in Lake Taihu

Abstract: Lake Taihu is the third largest freshwater lake in China and is contaminated with xenoestrogens associated with high population density, intensive livestock and aquatic breeding activities. A field study in Lake Taihu was conducted using the goldfish (Carassius auratus) as an indicator organism. Several biological markers were selected to assess the extent of estrogenic contamination. Changes in serum vitellogenin (VTG), and gill 7-Ethoxyresorufin-O-deethylase (EROD), glutathione-S-transferase (GST) and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…As the levels of VTG in fish were found to increase with the periods of exposure when exposed environmental estrogens (Lu et al 2011), VTG in goldfish were determined only after 7 days of exposure in this study. Serum VTG levels were measured following a competitive enzyme-linked immunosorbent assay (ELISA), as described by Rempel et al (2006).…”
Section: Enzyme Assaysmentioning
confidence: 91%
“…As the levels of VTG in fish were found to increase with the periods of exposure when exposed environmental estrogens (Lu et al 2011), VTG in goldfish were determined only after 7 days of exposure in this study. Serum VTG levels were measured following a competitive enzyme-linked immunosorbent assay (ELISA), as described by Rempel et al (2006).…”
Section: Enzyme Assaysmentioning
confidence: 91%
“…The EDCs in the water environment have posed threats to human health via drinking and/or food chain (Chang et al 2009;Falconer et al 2006). The EDCs were also widely detected in some lakes, such as Donghu Lake (Jin et al 2013), Lake Malta (Zgola-Grzeskowiak et al 2010), Dianchi Lake (Wang et al 2012), and Lake Taihu (Lu et al 2011). In this study, bisphenol A (BPA), 4-nonylphenol (NP), 4-octylphenol (OP), 17α-ethinylestradiol (EE2), estrone (E1), 17α-estradiol (αE2), 17β-estradiol (βE2), and estriol (E3) were selected for study of the occurrence and distribution of estrogens in the East Dongting Lake and Honghu Lake.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that 4-OP caused significant increase in GST activity. Increased GST activity has also been reported in various fish species exposed to environmental contaminants such as polychlorinated biphenyls, polyaromatic hydrocarbons and estrogens (Otto and Moon 1996;Lu et al 2011). Du et al (2008) also reported elevated levels of hepatic GST activity in rabbitfish (Siganus oramin) exposed to t-OP, possibly related to increased free radical production.…”
Section: Discussionmentioning
confidence: 82%